Probing Vibrational Symmetry Effects and Nuclear Spin Economy Principles in Molecular Spin Qubits - Santanni, Fabio (Inorg Chem, 2020)
[Image: see text] The selection of molecular spin qubits with a long coherence time, T(m), is a central task for implementing molecule-based quantum technologies. Even if a sufficiently long T(m) can be achieved through an efficient synthetic strategy and ad hoc experimental measurement procedures, many factors contributing to the loss of coherence still need to be thoroughly investigated and understood. Vibrational properties and nuclear spins of hydrogens are two of them. The former plays a paramount role, but a detailed theoretical investigation aimed at studying their effects on the spin dynamics of molecular complexes such as the benchmark phthalocyanine (Pc) is still missing, whereas the effect of the latter deserves to be examined in detail for such a class of compounds. In this work, we adopted a combined theoretical and experimental approach to investigate the relaxation properties of classical [Cu(Pc)] and a Cu(II) complex based on the ligand tetrakis(thiadiazole)porphyrazine (H(2)TTDPz), characterized by a hydrogen-free molecular structure. Systematic calculations of molecular vibrations exemplify the effect of normal modes on the spin–lattice relaxation process, unveiling a different contribution to T(1) depending on the symmetry of normal modes. Moreover, we observed that an appreciable T(m) enhancement could be achieved by removing hydrogens from the ligand.